Pengaruh Aktivitas Pemasaran Dan Aset Tidak Berwujud Terhadap Nilai Perusahaan (Studi Perusahaan Makanan dan Minuman Terdaftar di Bursa Efek Indonesia Periode 2016 - 2019) - Hamim Jazuli; Erfan M (DPPM Universitas Pelita Bangsa, 2022)
This study aims to analyze the effect of marketing activities and intangible assets on firm value. This type of research is a quantitative research. The population in this study is the food and beverage industry sub-sector companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. The sampling technique uses purposive sampling, and a total sample of 14 companies is obtained. The data collection technique uses secondary data that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results show that marketing activities have a negative and insignificant effect on firm value, intangible assets have a negative and insignificant effect, liquidity has a negative and significant effect, profitability has a negative and insignificant effect, solvency has a negative and insignificant effect, marketing activities, intangible assets, liquidity, profitability and profitability simultaneously affect the value of the company.